2019
DOI: 10.21203/rs.2.9579/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between dynamic obesity and mortality in patients with first-ever ischemic stroke: a hospital-based prospective study

Abstract: Background and Purpose: Although obesity is an established risk factor for the occurrence of a primary stroke, the association between obesity with post-stroke mortality remains unclear. We evaluated the association of dynamic obesity status with mortality among first-ever stroke survivors in China. Methods: Data from 775 patients with first-ever ischaemic stroke from a longitudinal study, 754 patients were categorized 4 categories of BMI (underweight, normal weight, overweight and obese) and 2 categories of W… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Of the 14 prospective cohort studies examining the relationship between BMI and outcomes, 149 107 participants (46% females) diagnosed with stroke were included. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Mean age across the studies ranged from 54.2 to 78.0 years. All-cause mortality was determined at three months for three studies 17,21,27 at six months for one study 18 and at 12 months or longer in the remaining ten studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 14 prospective cohort studies examining the relationship between BMI and outcomes, 149 107 participants (46% females) diagnosed with stroke were included. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] Mean age across the studies ranged from 54.2 to 78.0 years. All-cause mortality was determined at three months for three studies 17,21,27 at six months for one study 18 and at 12 months or longer in the remaining ten studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All-cause mortality was determined at three months for three studies 17,21,27 at six months for one study 18 and at 12 months or longer in the remaining ten studies. [14][15][16]19,20,[22][23][24][25][26] Poor functional status was ascertained by the modified Rankin Scale (mRS), Barthel Index (BI) and Functional Independence Measure. This was measured at three months in two studies 16,20 and at six months in one study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the remaining 196 articles assessed for eligibility, 163 articles were excluded for having the same study population ( n = 5); for having a sample size < 100 ( n = 3); for lack of data on obesity, overweight, or underweight ( n = 108); or for not investigating the concerned outcome of stroke ( n = 47). Finally, 33 articles including 84,660 patients were included in the full analysis [9–41]. The detailed process of study selection is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%